The effect of resting morphological lip shape during lip movement: A three-dimensional motion analysis study. Issue 6 (June 2020) - Nasir, Siti Hajjar; Popat, Hashmat; Richmond, Stephen
Abstract: Purpose: The aim of this study was to determine the influence of different morphological lip shape during lip movement. Method: A sample of 80 individuals with three-dimensional facial images at rest and during speech were recorded. Subjects were asked to pronounce four bilabial words in a relaxed manner and scanned using the 3dMDFace™ Dynamic System at 48 frames per second. Six lip landmarks were identified at rest and the landmark displacement vectors for the frame of maximal lip movement for all six visemes were recorded. Principal component analysis was applied to isolate relationship between lip traits and their registered coordinates. Eight specific resting morphological lip traits were identified for each individual. The principal component (PC) scores for each viseme were labelled by lip morphological trait and were graphically visualized as ellipses to discriminate any differences in lip movement. Results: The first five PCs accounted for up to 95% of the total variance in lip shape during movement, with PC1 accounting for at least 38%. There was no clear discrimination between PC1, PC2 and PC3 for any of the resting morphological lip traits. Conclusion: Lip shapes during movement are more uniform between individuals and resting morphological lip shape does not influence movement of the lips. Abstract : Anatomy; Lip shape; Lip motion; 3dMD; Lip phenotypes; PCA